The behaviour of spudcan footings on clay subjected to combined cyclic loading - Vlahos, G; Cassidy, M; Byrne, B (2006)
This paper presents an improved numerical 'force resultant model' for spudcan foundations that can be used within a structural analysis of a mobile drilling unit. The model incorporates hysteretic behaviour for pre-yield 'elastic' movements by using a hyperplasticity formulation [Houlsby GT, Puzrin AM. Rate-dependent plasticity models derived from potential functions. Journal of Rheology 2002;46(1):113-26] for the moment-rotation response in the 'elastic' stiffness matrix. The formulation is embedded within an existing single surface plasticity model [Martin CM, Houlsby GT. Combined loading of spudcan foundations on clay: Numerical modelling. Géotechnique 2001;51(8):687-99] that would typically use linear elastic stiffness coefficients. The hyperplastic model has been calibrated against single footing tests carried out using a sophisticated three degree-of-freedom loading device at Oxford University. These loading tests were specific to the load paths experienced by spudcan foundations of large jack-ups in deep water. Further experimental work at the University of Western Australia involved applying monotonic and cyclic loading to a model three-legged jack-up [Vlahos G. Physical and numerical modelling of a three-legged jack-up structure on clay soil. Ph.D. thesis. Australia: University of Western Australia; 2004; Vlahos G, Martin CM, Prior MS, Cassidy MJ. Development of a model jack-up unit for the study of soil-structure interaction on clay. International Journal of Physical Modelling in Geomechanics 2005;5(2):31-48]. The experimental results from jack-up tests were compared to numerical simulations using a finite element model with the single surface plasticity foundation model incorporating (i) linear springs, and (ii) non-linear hyperplastic springs. The latter formulation showed an improved correlation with the experimental results. © 2006 Elsevier Ltd. All rights reserved.